Recent Patent on a Hydrodynamic Lubricated Step Bearing by Preventing the Boundary Slippage - Zhang, Yongbin; Guan, Linyue (Recent Patents on Mechanical Engineering, 2018)
Background: In the hydrodynamic lubricated step bearing with a small ratio of the outlet zone width to the inlet zone width, the boundary slippage frequently occurs on both the contact surfaces in the outlet zone and on the moving contact surface in the inlet zone in the condition of heavy loads and high sliding speeds. Thus, the load-carrying capacity of the bearing is greatly reduced but the friction coefficient of the bearing is significantly increased, as compared to the calculation results from conventional hydrodynamic lubrication theory. The boundary slippage in this bearing is thus very harmful. Objective: The study aimed to introduce the hydrodynamic step bearings in these operating conditions with high load-carrying capacities and low friction coefficients by preventing the boundary slippage on the bearing surfaces as registered in the patent. Methods: The analytical results are presented for the carried load and friction coefficient of this kind of bearing with natural contact surfaces by considering the contact-fluid interfacial slippage. The calculated carried load and friction coefficient of the bearing are compared with those calculated from the conventional hydrodynamic lubrication theory for the same operating conditions. The invented bearing is then proposed by preventing the boundary slippage for significantly improving the overall performance of the bearing. Results: It is shown that due to the occurrence of the boundary slippage, the performance of the studied bearing with natural contact surfaces is overall severely deteriorated including the drop of its loadcarrying capacity and the significant increase in its friction coefficient. The bearing thus works in a bad condition. The invented bearing by preventing the occurrence of the boundary slippage thus has overall improved performances. Conclusion: The overall performance of the studied bearing can be greatly improved by eliminating the boundary slippage occurrence. The working condition of the bearing can thus be significantly bettered.
Keywords: load